Troubles digestifs du sportif - Watelet, J. (Science & Sports, 2011)
Exercise-related gastrointestinal symptoms are very frequent events in long distance runners and resorting to self-treatment. Physiopathological mechanisms are complex because they are combined. They involve three main factors: ischemic, driving and mechanic. Individual and environmental parameters also play a role. Ischemia is considered as the most serious factor. However all cases published are of limited clinical incidence with a favorable prognosis when they are quickly cared. The prevention of these digestive disorders should be personalized. It rests essentially with a training adapted to the expected effort and with nutritional measures. Resort to pharmacopoeia is possible but limited and bases itself mainly on gastric demulcents and antacids.